The Measurement Tool for Analyzing the Influence of e-WOM and Brand Image on Purchase Decision at Make Over Brands - Syarifudin, Nazwa; Indrawati, Indrawati (ADPEBI, 2024)
In March 2023, 42% of 1,050 respondents in Indonesia selected cosmetic and body care products as their most sought-after category, making it the third most popular for online purchases. This study aims to develop a measurement tool to analyze the influence of Electronic Word of Mouth (e-WOM) and brand image on purchase decisions, focusing on Halal brands. Using Smart PLS for structural equation modeling, a purposive sampling method targeted 30 respondents who purchased Make Over products. The pilot test confirmed the tool's validity and reliability, comprising 7 variables and 34 items, making it suitable for further research.